A systematic literature mapping of risk analysis of big data in cloud computing environment - Yusof Ali, Hazirah Bee; Abdullah, Lili Marziana; Kartiwi, Mira; Nordin, Azlin; Salleh, Norsaremah; Awang Abu Bakar, Normi Sham (IOP Publishing, 2018)
This paper investigates previous literature that focusses on the three elements: risk assessment, big data and cloud. We use a systematic literature mapping method to search for journals and proceedings. The systematic literature mapping process is utilized to get a properly screened and focused literature. With the help of inclusion and exclusion criteria, the search of literature is further narrowed. Classification helps us in grouping the literature into categories. At the end of the mapping, gaps can be seen. The gap is where our focus should be in analysing risk of big data in cloud computing environment. Thus, a framework of how to assess the risk of security, privacy and trust associated with big data and cloud computing environment is highly needed